Human Capital and Economic Growth - How Strong is the Nexus? - Marinko Škare; Sabina Lacmanovic (Amfiteatru Economic Journal, 2016)
The link between human capital and economic growth still remains unexplained because of the measurement issues connected to the human capital stock. This study investigates the link between human capital stock and economic growth using inclusive wealth index and ratio of engaged to actively disengaged employees as proxy for human capital stock. Data from the global workplace and inclusive wealth reports are used in order to provide an international comparison of the link between human capital and inclusive wealth. Cross country comparison show human capital largerly contribute to the inclusive wealth formation. Formal education is important but also motivating working environment is needed to achieve sustainable economic growth. The finding further indicates that standard human capital growth model should be revised taking into the account variables addressing sustainable growth (not just growth) and environmental variables (work conditions) affecting human capital stock. Countries encouraging investments in the development of individuals both through formal education and inspiring work environments achieve higher sustainable economic growth.
Keywords: E21; E24; J24; O00; Q56; 330; human capital; economic growth; inclusive wealth; cross-country comparison; employees engagement